2021
DOI: 10.3390/ijms23010143
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Biodiversity of Protein Targeting and Protein Transport Related to the Endoplasmic Reticulum

Abstract: Looking at the variety of the thousands of different polypeptides that have been focused on in the research on the endoplasmic reticulum from the last five decades taught us one humble lesson: no one size fits all. Cells use an impressive array of components to enable the safe transport of protein cargo from the cytosolic ribosomes to the endoplasmic reticulum. Safety during the transit is warranted by the interplay of cytosolic chaperones, membrane receptors, and protein translocases that together form functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 442 publications
(648 reference statements)
0
23
0
1
Order By: Relevance
“…Supporting the data from the co-immunoprecipitation and peptide spot arrays, the live cell protein-protein interaction assay demonstrated that the C-terminus of TMEM109 interacts with the N-terminus of hSnd2 (Figure 5E). In general, protein targeting receptors guide incoming polypeptides to a suitable translocase (Pool, 2022; Tirincsi et al 2022; Jomaa et al 2017 and 2021), hence crosslinking data showed that SRα binds to the Sec61 translocon (Jadhav et al 2015). Similarly, we found TMEM109 to interact strongly with the C-terminus of TRAPα and less efficiently with the C-terminus of Sec61α (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Supporting the data from the co-immunoprecipitation and peptide spot arrays, the live cell protein-protein interaction assay demonstrated that the C-terminus of TMEM109 interacts with the N-terminus of hSnd2 (Figure 5E). In general, protein targeting receptors guide incoming polypeptides to a suitable translocase (Pool, 2022; Tirincsi et al 2022; Jomaa et al 2017 and 2021), hence crosslinking data showed that SRα binds to the Sec61 translocon (Jadhav et al 2015). Similarly, we found TMEM109 to interact strongly with the C-terminus of TRAPα and less efficiently with the C-terminus of Sec61α (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“…So far, four protein targeting pathways which can deliver precursor polypeptides to the Sec61 protein conducting channel in the ER membrane in human cells have been described, i.e. the SRP/SR-, the SGTA/TRC/WRB-, the SND- and the PEX19/PEX3-pathway (Ast et al, 2013; Borgese et al, 2019; Tirincsi et al, 2022; Pool, 2022). While there are functional and structural insights available for the molecular mechanisms and client spectra of the SRP- and TRC-dependent pathways, little is known about the composition and mechanistic function of the human SND pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next section of the Special Issue deals with the machineries for membrane insertion and translocation of proteins in the ER membrane with special emphasis on the central role of the Sec61 complex. Here, A. Tirincsi et al [8] provide up to date insights into the connections between the different targeting and translocation/insertion machineries, while P. Bhadra and V. Helms [9] as well as M. Liaci and F. Förster [10] focus on molecular dynamics and structural aspects of the Sec61 complex, respectively. This part of the Special Issue is finished off by S.-j.…”
mentioning
confidence: 99%